2007
DOI: 10.1038/emm.2007.57
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1-induced PINCH-1-ILK-α-parvin complex formation regulates mesangial cell proliferation and hypertrophy

Abstract: TGF-β1-induced glomerular mesangial cell (GMC) injury is a prominent characteristic of renal pathology in several kidney diseases, and a ternary protein complex consisting of PINCH-1, integrin-linked kinase (ILK) and α-parvin plays a pivotal role in the regulation of cell behavior such as cell proliferation and hypertrophy. We report here that PINCH-1-ILK-α-parvin (PIP) complex regulates the TGF-β1-induced cell proliferation and hypertrophy in cultured rat GMCs. When GMCs were treated with TGF-β1 for 1, 2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Lee., 2000), and hypoxia (Lee et al, 2009). It is well documented that HG enhances TGF-β1 expression in mesangial cells, vascular endothelial cells, and retinal pigment epithelial cells (Wu et al, 2009;Chen et al, 2007;Kim et al, 2007aKim et al, , 2007bHayashida and Schnaper, 2004;Isono et al, 2000). The increased TGF-β1 activity is considered to contribute to the development of endothelial dysfunction and micro-and macrovascular complications in diabetes mellitus diabetic nephropathy (Hayashida and Schnaper, 2004;Belmadani et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Lee., 2000), and hypoxia (Lee et al, 2009). It is well documented that HG enhances TGF-β1 expression in mesangial cells, vascular endothelial cells, and retinal pigment epithelial cells (Wu et al, 2009;Chen et al, 2007;Kim et al, 2007aKim et al, , 2007bHayashida and Schnaper, 2004;Isono et al, 2000). The increased TGF-β1 activity is considered to contribute to the development of endothelial dysfunction and micro-and macrovascular complications in diabetes mellitus diabetic nephropathy (Hayashida and Schnaper, 2004;Belmadani et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…Protein kinase C and Akt signaling as well as the transcription factor AP-1 are involved in glucose-induced TGF-β1 upregulation in mesangial cells and human MSCs (Wu et al, 2009;Ryu et al, 2010). ERK1/2 and P38 MAPK pathways also play an important role in HG-induced increase in TGF-β1 expression in mesangial cells, vascular endothelial cells, and retinal pigment epithelial cells (Chen et al, 2007;Kim et al, 2007aKim et al, , 2007bHayashida and Schnaper, 2004;Isono et al, 2000;Fujita et al, 2004). In the present study, we demonstrated that HG upregulated TGF-β1 expression in rat MAPCs through ERK1/2-mediated inhibition of STAT3 signaling.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Transforming growth factor-β 1 (TGF-β 1 ) can induce the accumulation of extracellular matrix (ECM) components, including collagens, fibronectin (FN) and laminin in the glomeruli and the interstitium of the kidney. TGF-β 1 expression regulates PINCH-1-integrin-linked kinase (ILK)-alpha-parvin complex formation and contributes to glomerular mesangial cell (GMC) proliferation and hypertrophy [4]. ILK, a cytoplasmic-binding serine/threonine protein kinase, is physically connected to the actin cytoskeleton and actin-binding protein CH-ILKBP, which is an important step in the development and progression of glomerular failure observed in several kidney diseases [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the null mice also display female sterility due to defective ovarian and uterine function (Fero et al, 1996;Chien et al, 2007;Kim et al, 2007). The tumor suppressive activity of p27 KIP1 using null mice was first demonstrated by development of adenomas in the intermediate lobe of the pituitary gland, and by their inclination to develop tumors more easily when challenged with chemical carcinogens or irradiation (Nakayama et al, 1996).…”
Section: Introductionmentioning
confidence: 99%